COPYRIGHT LAW AND INVESTMENT IN INDONESIA: A LEGAL BRIDGE - Rufinus Hotmaulana Hutauruk; Hari Sutra Disemadi; Lu Sudirman; David Tan (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract The nexus between investment and intellectual property often intersects with the international movement of capital. A robust legal structure is essential in comprehending potential issues, particularly concerning copyrights, which is one of the most frequently utilized intellectual property rights systems within the Indonesian economy. Consequently, this study seeks to pinpoint the elements linking these two notions within the framework of copyright regulations. Findings indicate that specific challenges may result in protracted and intricate administrative processes, as revealed through normative legal research methodologies. Concurrently, a thorough analysis employing the statutory approach reveals that these challenges stem from normative constraints, which may deter investors from engaging in the Indonesian economic landscape. Abstrak Hubungan antara investasi dan hak kekayaan intelektual sering kali saling terkait dengan arus modal global. Struktur hukum yang kokoh sangat penting untuk memahami potensi masalah, khususnya terkait hak cipta, yang merupakan salah satu sistem hak kekayaan intelektual yang paling sering digunakan dalam ekonomi Indonesia. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang menghubungkan kedua konsep ini dalam konteks regulasi hak cipta. Temuan menunjukkan bahwa tantangan-tantangan tertentu dapat mengakibatkan proses administratif yang panjang dan rumit, sebagaimana terungkap melalui metodologi penelitian hukum normatif. Sementara itu, analisis menyeluruh yang menggunakan pendekatan statutori menunjukkan bahwa tantangan-tantangan ini berasal dari pembatasan-pembatasan normatif, yang dapat menghalangi investor untuk terlibat dalam lanskap ekonomi Indonesia.